A Critical Assessment of the Regulatory Framework for Oil and Gas Decommissioning in Nigeria - Omotuyi, Opeyemi Yetunde (Journal of Sustainable Development Law and Policy, 2025)
Oil and gas production have been ongoing in Nigeria since the first major discovery of oil in commercial quantity in 1956. With over sixty years of exploitation, there is a tendency that several oil fields may be approaching the end of their viable lifespan. Moreover, with the increasing agitation against global warming and climate change, and the attendant shift towards energy transition and sustainable development, a wave of decommissioning in the oil and gas sector is to be expected globally. Since Nigeria is identifying with the energy transition agenda, the discourse on decommissioning is germane to the Nigerian oil and gas industry, especially because a move to cleaner energy sources will necessitate the decommissioning of several oil fields in the country. To ensure an effective decommissioning regime however, there must be established clear and enforceable rules and regulations for decommissioning in the oil and gas industry. Such rules and regulations must also address major issues and challenges attributable to decommissioning oil and gas projects generally. Against this backdrop, this study explores the various legal regimes applicable to the decommissioning of oil and gas projects in Nigeria, with the aim of identifying the adequacy or otherwise of such laws. It was found that the existing legal regime, where considered together, provides adequately for decommissioning issues and challenges in the Nigerian oil and gas sector. Notwithstanding, the study found few challenges that may still hinder effective decommissioning processes in Nigeria. Therefore, the study concluded by proffering suitable recommendations that can promote the objectives of decommissioning in the Nigerian oil and gas sector.